Prototipe Pemandu Parkir Mobil Dengan Output Suara Manusia Mengunakan Mikrokontroler Arduino Uno - Pindrayana, Kadek; Indra Borman, Rohmat; Prasetyo, Bagas; Samsugi, Samsugi (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2018)
To facilitate the parking of the car to be efficient parking equipment was needed by using the distance with objects. In this research, the development of prototype of car parking guide by displaying information by using centimeter or meter unit and using sound output to facilitate the user in parking their vehicle. From the analysis and testing of prototype car park guides with human voice output indicates that this prototype can give good results. Ultrasonic sensor SRF05 can work well but in the sensor distance of more than 3 meters cannot send data